Ontogenetic shifts in plant ecological strategies - Dayrell, Roberta L. C.; Arruda, André J.; Pierce, Simon; Negreiros, Daniel; Meyer, Pablo B.; Lambers, Hans; Silveira, Fernando A. O. (Functional ecology, 2018)
Ontogenetic shifts in plants are ubiquitous, but their ecological and evolutionary significance remain largely unknown. Juveniles have few opportunities to accumulate sufficient biomass to withstand damage, whereas adults allocate resources to reproduction. Thus, age‐specific environmental filters are expected to drive selection towards specific resource‐investment strategies for each developmental stage. We tested whether species exhibited strategies that favour faster rates of biomass accumulation during early developmental stages to cope with vulnerability, shifting towards habitat‐dependent strategies to optimise resource acquisition and use later on. We also hypothesised that juveniles exhibit greater intraspecific variability of strategies than adults, as a result of continuous filtering of traits throughout the plant’s development towards adulthood. We measured key leaf traits—leaf area (LA), leaf dry matter content (LDMC) and specific leaf area (SLA)—and calculated scores for competitor (C), stress‐tolerator (S), ruderal (R) strategies of the CSR system for juveniles of 54 species and conspecific adults of 27 species naturally occurring either in unproductive (grassland) or productive (forest) habitats. Juveniles exhibited higher SLA and LA and lower LDMC, and thus a more R‐strategy in both habitats when compared with adults, but were not necessarily “R” in absolute terms. We also found smaller intraspecific variation for the R‐strategy in adults compared with juveniles in both habitats, whereas the variation of the other strategies was habitat dependent. Ontogenetic shifts in ecological strategies appear to have been selected as a response to ontogeny‐dependent filters. Thus, strategies that favour less costly leaves and faster growth rates (relatively R‐selected) in juveniles shift towards C and/or S strategies in adulthood, depending on habitat productivity. Nevertheless, habitat‐dependent specialisation seems to be a major driver of ecological strategy selection in juveniles. Our study reveals ontogeny‐dependent strategies, offering a new approach to integrate plant development and functional specialisation. A plain language summary is available for this article. Plain Language Summary